Isolasi Dan Identifikasi Bakteri Termofil Penghasil Amilase Dari Sumber Air Panas Lejja Sulawesi Selatan - Arfah, Rugaiyah A.; Patong, Abd. Rauf; Ahmad, Ahyar; Djide, M. Natsir (Al-Kimia, 2014)
A Research isolation and identification of bacteria termofil amylase from hot springs Lejja South Sulawesi has been done. This study aims to characterize the morphological, biochemical, genus and species of bacteria producing the enzyme amylase. The method used in this study through the stages: 1) Skrening and isolation of bacteria by means of as much as 1.0 mL of sample dilution plated on Petri dishes containing agar medium, then incubated for 20-24 hours at 50 °C, colonies of bacteria growing and has a colony morphology different character each taken 1 ose then etched into the amylolytic selective medium then incubated for 20-24 hours at 40oC and 50oC. Colonies that grew on selective media is scratched quadrant amylolytic to obtain pure isolates. Pure bacterial isolates taken 1 ose then grown in selective medium for 48 h at 50° C, bacterial isolates were grown spilled iodine solution (2% I2 and 0.2% KI) when there is a clearing zone around the colony indicated as the enzyme-producing bacterial isolates termofil amylase; 2) termofil characterization of bacterial isolates in microscopy with Gram stain; 3) isolates selected biochemical tests performed according to the method Bergey’s Manual and Systematic of Bacteriology. Results of screening and isolation of 10 bacterial isolates obtained amylase through iodine test, selected 2 isolates, 1 isolate from water samples RSAII-1B and 1 isolates from water samples mixed sediment RSSII-4B, which has a diameter of clearing zone of 5.6 cm respectively and 5.15 cm; out such characterization results of gram stain microscopy showed that the 2 isolates including gram + and shaped bacillus, the colony morphology as observed macroscopically, microscopy and biochemical test results obtained RSAII isolates and isolates RSSII-1B-4B is a Bacillus sp.